Tinjauan Hukum Atas Wewenang Pemerintah Dalam Pencegahan Penghindaran Pajak - Syafari, Herdin; Miharja, Marjan (FOCUS, 2025)
The provisions in Article 32 and Article 43 of Government Regulation No. 55 of 2022 are to provide an authority to the Minister of Finance in determining expenses that cannot be deducted from gross income (non-deductible expenses), which are considered to exceed the limits of authority regulated in Article 18 of the HPP Law. Article 18 of the HPP Law has expressly regulated the mechanism for preventing tax evasion, but does not include the authority as formulated in the PP, especially related to the imposition of fees on payments to foreign taxpayers whose receipts are not subject to income tax in their country of domicile. This research aims to examine the excesses of authority that have been delegated in Article 18 of Law No. 7 of 2021 concerning the Harmonization of Tax Regulations and its implications. This study uses normative legal research with a literature study on laws and regulations in Indonesia. The results of the study show that Articles 32 and 43 of Government Regulation Number 55 of 2022 have significant legal implications because they are considered to exceed the authority delegated in Article 18 of Law Number 7 of 2021 concerning the Harmonization of Tax Regulations. The provisions in this Government Regulation, especially related to the application of the substance over form doctrine and guidelines for the prevention of tax evasion, are not explicitly regulated in the HPP Law, thus creating potential conflicts in the regulatory hierarchy, legal uncertainty, and the risk of abuse of authority by tax authorities. In addition, the unclear limitation of authority in the guidelines set by the Minister of Finance also has the potential to increase legal disputes between taxpayers and the government. While it aims to improve tax compliance and prevent tax avoidance, it requires more detailed adjustments and guidelines to ensure its implementation is in line with the principles of legal certainty and regulatory hierarchy.